Effect of Sorghum bicolor L. and Moringa oleifera Leaf Flour Substitution on the Nutritional and Organoleptic Quality of Snack Bars for Type 2 Diabetes Mellitus Patients - Fawwiz Aulya Amin; Theresia Puspita; Komang Suwita (Universitas Islam Negeri Walisongo Semarang, 2025)
According to the International Diabetes Federation (IDF), the prevalence of type 2 diabetes mellitus (DM) had increased from 10.5% in 2021 to 11.1% in 2025. The need for the development of functional foods can support dietary management in diabetes sufferers. The purpose of this study was to analyze the effect of substituting sorghum flour and moringa leaf flour on nutritional quality (moisture, ash, protein, fat, carbohydrate content, and energy), organoleptic quality (color, aroma, taste, and texture), and functional quality (fibre and antioxidant activity) of snack bars for type 2 diabetics. This study used a Completely Randomized Design (CRD) using three levels of treatment with the following proportions of sorghum flour to moringa leaf flour: P1 (85:15), P2 (90:10), and P3 (95:5). A total of 25 semi-trained panelists were selected using a purposive sampling technique. Data’s were analyzed using One-Way ANOVA for nutritional parameters and functional quality, Kruskal Wallis test for organoleptic data with a 95% confidence level. The results showed that the substitution of sorghum flour and moringa leaf flour had a significant effect on protein, fibre, and snack bar taste (p<0.05). However, it had no significant effect on moisture, ash, fat, carbohydrate, color, aroma, texture, or antioxidant activity of snack bars. It was also found that the best treatment level was P3 (95:5). The snack bar formulation based on sorghum and moringa leaves has the potential to be developed as a low glycemic index functional food that supports diet management in type 2 DM patients.